Long-term nutrient management in an intensive rice-wheat cropping system improves the quantities, qualities, and availability of soil sulfur - Meena, Sunita Kumari; Dwivedi, B. S.; Meena, Mahesh C.; Datta, S. P.; Singh, Vinod Kumar; Mishra, R. P.; Chakraborty, Debashish; Dey, Abir; Meena, Vijay Singh (Frontiers in Sustainable Food Systems, 2022)
In the last few decades, the deficiency of sulfur (S) has been noticed in the agricultural soils of India. Meanwhile, researchers reported that S plays a significant role in the productivity of the rice-wheat cropping system (RWCS). For the quantification of S response, a long-term field experiment was started at the Indian Council of Agricultural Research-Indian Institute of Farming Systems Research (ICAR-IIFSR), Modipuram, India. In total, 7 nutrient supply options were applied, i.e., organic, mineral fertilizer in the combination of integrated plant nutrition system (IPNS), and IPNS + berseem (B)/IPNS + cowpea (C) in the S availability of the soil in the RWCS. The results showed that the highest contribution in S availability by the total S (39%) is followed by the organic S (35%), sodium bicarbonate extractable sulfur (NaHCO3-ES; 7%), heat-soluble sulfur (SS; 7%), water-soluble sulfur (WSS; 4%), available S (4%), and inorganic S (4%) under different long-term nutrient supply options of RWCS. The continuous application of organic fertilizer and various IPNS options, such as the inclusion of pulses, significantly improved all S fractions in the soil and also offers an additional benefit in terms of sustainability of production and soil health as compared to the inorganic fertilizer fields. Overall, the results showed that IPNS showed its superiority over the rest of the treatment. The results also supported that the inclusion of pulses gives a further gain in terms of sulfur availability in soil systems under RWCS.